Editorial : Vaccination strategies against ruminant infectious diseases - Del Medico Zajac, Maria Paula; Moyano, Roberto Damian; Colombatti Olivieri, Maria Alejandra (Frontiers Media, 2023)
Ruminant infectious diseases cause economic impact through losses in animal production and human health. Most of the commercially available veterinary vaccines are live attenuated or inactivated which induce different degrees of efficacy, i.e., decrease in clinical symptoms, pathogen dissemination, etc. (1, 2). The use of these vaccines has greatly enhanced ruminant and public wellbeing around the world, however, in some cases, they have limitations in their ability to induce protective immunity. Thus, rationally designed vaccines along with specific immunization schemes are required to achieve the desired outcome of vaccination against an infectious disease. Vaccine safety is another important consideration, not only in terms of potential risks to the target animal (to which the vaccine is administered), but also to the environment and to consumers of food derived from vaccinated animals (3).